Biological control of brown rot in stone fruit using Bacillus amyloliquefaciens CPA-8 under field conditions. (December 2017) - Gotor-Vila, A.; Teixidó, N.; Casals, C.; Torres, R.; De Cal, A.; Guijarro, B.; Usall, J.
Abstract: Different treatments based on the biocontrol agent (BCA) Bacillus amyloliquefaciens CPA-8 to control brown rot under field conditions were evaluated as alternative to chemical applications. As part of a well-designed disease program that enables the integration of BCAs into cropping systems, testing of the sensitivity of Monilinia laxa and Monilinia fructicola at different doses of CPA-8 were conducted in stone fruit under laboratory conditions. CPA-8 dose of 10 7 CFU mL −1 reduced more than 60.0 and 75.5% of brown rot incidence and severity, respectively. Once in the orchard, different degree of biocontrol activity was obtained depending on the inoculum pressure, which was mainly associated with meteorological conditions. Under drastic disease pressure, neither CPA-8 treatment nor the chemicals controlled the disease at harvest and only the chemical treatment reduced postharvest brown rot incidence. However, when Monilinia spp. incidence was close to the standard levels recorded in the area, treatments based on CPA-8 formulations proved to be efficacious. At harvest, BA3, BA4 treatments (CPA-8 optimised products) and PF + BA3 treatment ( Penicillium frequentans combined with CPA- 8) reduced Monilinia spp. incidence compared to the control (54.7–64.1%) and similar to the chemicals. At postharvest, almost all CPA-8-based treatments (except PF + BA3) controlled the pathogen with BA4 treatment being as much effective as the chemicals (50.3% of disease reduction). Finally, the population dynamics of CPA-8 on treated fruit surface remained after treatment application, at harvest and at postharvest shelf-life (>10 4 CFU cm −2 ). This study highlights the potential of B. amyloliquefaciens CPA-8 as alternative or complementary strategies to control Monilinia spp. Highlights: Under laboratory conditions CPA-8 at 10 7 CFU mL −1 most reduced brown rot disease. CPA-8 treatments were efficacious under standard Monilinia spp. levels in the field. BA4 treatment reduced postharvest brown rot similar to chemical applications. No CPA-8 effect was observed under high disease pressure in the field (>50%). CPA-8 on fruit remained after application, at harvest and at postharvest (10 4 CFU cm −2 ).